1510 Percutaneous Coronary Intervention vs Coronary Artery Bypass Grafting in Left Main Coronary Artery Disease. A Systematic Review and Meta-Analysis of Randomized Controlled Trials. (12th October 2021) - Hennessy, C; Henry, J A
Abstract: Aim: There is still no consensus whether percutaneous coronary intervention (PCI) is as safe and effective as coronary artery bypass grafting (CABG) for left main coronary artery (LMCA) disease. Recent updates from key clinical trials necessitated an updated examination of the literature on this topic. Method: A systematic search was performed of the MEDLINE (via PubMed), EMBASE, Cochrane and clinicaltrials.gov databases from inception to December 20 th, 2020. Selected studies were analysed using the random effects model. Outcomes measured included all-cause mortality, MACCE, myocardial infarction (MI), stroke and revascularization. Follow up points were 30 days, 1 year, 5 years and 10 years. Results: Six RCTs with a total population of 4700 were included in the analysis. For all-cause mortality PCI was non-inferior to CABG at all time points. MACCE favoured PCI at 30 days, and CABG at 5 years. No difference was seen at 1 year and 10 years. MI favoured CABG at 5 years follow up, with no difference seen at 30 days, 1 year or five years. For stroke, PCI was favourable to CABG at 30 days and 1 year, with no difference at 5 years and 10 years. Revascularisation favoured CABG at 1 year and 5 years, with no difference at other time-points. Conclusions: PCI may be considered as an alternative to CABG for uncomplicated LMCA disease. More complex lesions may still benefit from CABG. CABG may be of benefit where future revascularisation would rather be avoided. Further clinical trials examining this research question are needed.